A universal rolling circle amplification for label-free and highly specific nucleic acid sensing. Issue 84 (5th October 2022) - Sun, Mengxu; Liu, Birong; Li, Tong; Li, Chunrong; Duan, Wen-Jun; Xie, Baoping; Li, Min-Min; Chen, Jin-Xiang; Dai, Zong; Chen, Jun
Abstract : A universal rolling circle amplification was proposed for label-free and highly specific nucleic acid sensing. Abstract : Traditional RCA methods face some drawbacks including limited specificity and amplification templates with sequence dependence. Herein, a universal RCA (URCA) strategy for label-free nucleic acid sensing with high specificity was proposed, which could be used for sensing of different nucleic acids without redesigning or synthesizing new amplification templates. The URCA strategy also showed high accuracy for miRNA analysis in practical samples.